Pengaruh Profitabilitas dan Corporate Social Responsibility terhadap Nilai Perusahaan (Pada Perusahaan Manufaktur Terdaftar di BEI) - Ringan, Angelina Yenny (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to determine the influence of Profitability and Corporate Social Responsibility on company value. Data collection in this study is through documentation, namely collecting and reviewing secondary data in the form of audited financial statements and annual reports the data analysis method used is the panel data regression analysis method with the help of Eviews 9. The sample in this study was obtained using purposive sampling, so that a research sample of 20 companies from 170 populations in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period was obtained. The results of this study show that: (1) Profitability and Corporate Social Responsibility simultaneously have a positive and significant effect on the company's value. (2) Profitability partially has a positive and significant effect on the company's value. (3) Corporate Social Responsibility has a negative and significant effect on the company's value.